Complete Fermi surface mapping of Bi2Sr2CaCu2O8+x(001): Coexistence of short range antiferromagnetic correlations and metallicity in the same phase - Aebi, Philipp; Osterwalder, Jürg; Schwaller, P.; Schlapbach, Louis; Shimoda, M.; Mochiku, T.; Kadowaki, K. (My University, 1994)
The Fermi surface of Bi2Sr2CaCu2O8+x(001) has been mapped at nearly 6000 points in k space using angle-resolved photoemission at 300 K. We observe both features that are in good agreement with the local density calculation of Massidda, Yu, and Freeman [Physica (Amsterdam) 158C, 251 (1988)] and others that are missing in the calculation. Among those missing, most importantly, we find a c (2×2) superstructure on the Fermi surface strongly suggesting short range antiferromagnetic correlations. It is remarkable that this is evident in the metallic state and in the Fermi surface itself.